Are Technology Interruptions Impacting Your Bottom Line? An Innovative Proposal for Change. Issue 4 (9th November 2015) - Ledbetter, Tamera; Shultz, Sarah; Beckham, Roxanne
Abstract : BACKGROUND: Nursing interruptions are a costly and dangerous variable in acute care hospitals. Malfunctioning technology equipment interrupts nursing care and prevents full utilization of computer safety systems to prevent patient care errors. AIMS: This paper identifies an innovative approach to nursing interruptions related to computer and computer cart malfunctions. The impact on human resources is defined and outcome measures were proposed. A multifaceted proposal, based on a literature review, aimed at reducing nursing interruptions is presented. This proposal is expected to increase patient safety, as well as patient and nurse satisfaction. SETTING: Acute care hospitals utilizing electronic medical records and bar‐coded medication administration technology. PARTICIPANTS: Nurses, information technology staff, nursing informatics staff, and all leadership teams affected by technology problems and their proposed solutions. METHODS: Literature from multiple fields was reviewed to evaluate research related to computer/computer cart failures, and the approaches used to resolve these issues. RESULTS: Outcome measured strategic goals related to patient safety, and nurse and patient satisfaction. Specific help desk metrics will demonstrate the effect of interventions. CONCLUSIONS: This paper addresses a gap in the literature and proposes practical and innovative solutions. A comprehensive computer and computer cart repair program is essential for patient safety, financial stewardship, and utilization of resources.